Music, Place, and the Everyday Sacred: Libby Larsen and Lessons in Environmental Awareness. Issue 3 (3rd May 2016) - Von Glahn, Denise
Abstract : Across centuries and cultures, mountains and gardens have been identified with the sacred; they are privileged places for encounters with the divine; they materialise moral force. But they are also contested places whose meanings and values vary. This article considers the ways American composer, Libby Larsen, has musicalised the multivalence of gardens and mountains in two pieces, In a Winter Garden, and Up Where the Air Gets Thin. It frames the discussion within the context of four axioms for understanding the character of sacred places proposed by Belden C. Lane, a scholar of theological studies, in his book Landscapes of the Sacred: Geography and Narrative in American Spirituality. In both works Larsen invites listeners to contemplate one reading of these places and to act on the lessons contained within the natural world.